Saliva-derived extracellular vesicles: a promising therapeutic approach for salivary gland fibrosis - Boyuan Peng; Xufei Guo; Jialing Kang; Shijiao Pan; Lili Wei; Lianhao Wang; Bo Li; Guangli Han; Yong Cheng (Journal of Translational Medicine)
Abstract Background Salivary gland (SG) fibrosis is characterized by aberrant extracellular matrix deposition and myofibroblast activation, leading to irreversible glandular dysfunction. Current treatments remain ineffective in reversing fibrosis, necessitating novel therapeutic strategies. Methods We investigated the anti-fibrotic effects of saliva-derived extracellular vesicles (sEV) through in vitro and in vivo approaches. Histopathological analysis assessed collagen deposition and myofibroblast activation in SG tissues. Human SG fibroblasts (hSGFs) and SG organoids were treated with sEV to evaluate their effects on TGF-β-induced fibrogenic activity, including migration, collagen production, and myofibroblast activation. Network analysis of exosomal miRNAs and integration of RNA sequencing with sEV miRNA-seq were performed to identify key regulatory pathways. A Wharton’s duct ligation model was used to examine the therapeutic potential of local sEV administration. Results sEV treatment significantly attenuated TGF-β-induced fibrogenic activity in hSGFs and SG organoids, suppressing migration, collagen production, and myofibroblast activation. Bioinformatics analysis revealed a synergistic regulatory effect of sEV-derived miRNAs on fibrosis-associated pathways, with STAT3 identified as a key mediator. In vivo, local sEV administration reduced SG fibrosis, preserved acinar structure, and inhibited STAT3 nuclear translocation in fibroblasts. Conclusion Our findings demonstrate that sEV exerts potent anti-fibrotic effects by modulating STAT3 signaling, offering a promising cell-free therapeutic strategy for SG fibrosis. These results highlight the potential of sEV as a natural nanotherapy for fibrotic SG disorders. Graphical Abstract